2023
DOI: 10.3390/ijms241310463
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Mutational Landscape of Osteosarcomas Identifies Genes Related to Metastasis and Prognosis and Disrupted Biological Pathways of Immune Response and Bone Development

Abstract: Osteosarcoma (OS) is the most prevalent type of bone tumor, but slow progress has been achieved in disentangling the full set of genomic events involved in its initiation and progression. We assessed by NGS the mutational spectrum of 28 primary OSs from Brazilian patients, and identified 445 potentially deleterious SNVs/indels and 1176 copy number alterations (CNAs). TP53 was the most recurrently mutated gene, with an overall rate of ~60%, considering SNVs/indels and CNAs. The most frequent CNAs (~60%) were ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…Moreover, a recent study showed how the WES analysis in osteosarcoma is able to identify alteration in genes involved in the protein-protein networking on specific pathways implicated in skeletal system development [63].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study showed how the WES analysis in osteosarcoma is able to identify alteration in genes involved in the protein-protein networking on specific pathways implicated in skeletal system development [63].…”
Section: Discussionmentioning
confidence: 99%
“…Another group found that PD-L1 was induced by IRF8 and that in human OSA cells, PD-L1 and IRF8 were involved in growth and tumorigenicity, and that PD-L1 knockdown combined with doxorubicin treatment resulted in inhibition of cell growth [76]. Furthermore, a study identified that IRF8 was among one of the many genes deleted in >25% of cases, according to an analysis of 28 human OSA samples [77]. Our current study presents the expression of IFR8 in canine OSA.…”
Section: Discussionmentioning
confidence: 99%